Multi-dimensional networking and distributed computing services - Pathan, Al-Sakib Khan (IJIDCS Press, Bangladesh, 2012)
Various types of wired and wireless networks and their applications can be seen in many places now-a-days. In the past decade, we have witnessed a significant increase in the number of Internet users and technology hunters. With the aid of wireless communications and demand of flexible anytime, anywhere networking, many types of wireless self-organizing networks have already gained huge popularity among users. For wider support of wireless connectivity and developing easy-to-use technologies, substantial efforts are underway to reduce human intervention in the configuration, formation, and maintenance processes of these networks. Furthermore, different types of distributed computing technologies are widening the scope of our thinking and research issues in networking. The multi-dimensional research issues include wireless and mobility problems, routing protocols and algorithms, resource and service location protocols, performance evaluations of networking systems, ubiquitous systems, context aware ubiquitous environment, mechanisms to improve throughput over wireless links, network management and network security, and other related areas.